AN INTEGRATED CYBERSECURITY APPROACH: INTEGRATING WAZUH AND BASE CVE (MITRE) FOR VULNERABILITY MANAGEMENT IN A CORPORATE ENVIRONMENT - Noura Teixeira, Otávio; Danilo Mendonça, Eudes (Revista Gênero e Interdisciplinaridade, 2026)
The acceleration of digital transformation has broadened the attack surface of organizations and increased the demand for systematic processes for identifying, prioritizing, and mitigating vulnerabilities. This study proposes and evaluates the integration between the Wazuh open-source platform and the CVE (MITRE) vulnerability database, aiming to consolidate a unified flow of monitoring and decision support in risk management. The research was conducted in a real corporate environment, at Frigorífico Santa Cruz, with an applied and exploratory approach. The implemented solution enabled real-time monitoring, event correlation, and automated alert generation, supporting prioritization by criticality. The results indicated increased efficiency in identifying critical vulnerabilities and a reduction in the average incident response time, suggesting that the Wazuh–CVE integration can strengthen security governance and expand the operational response capacity in organizations with limited resources.